Book Reviews (International review of mission, 1972)
Book reviewed in this article: Vermittlung Zwischenkirchlicher Gemeinschaft. 50 Jahre Missionsgesellschaft Bethlehem Immensee. “The Evangelization of the World in this Generation.” The Resurgence of a Missionary Idea among the Conservative Evangelicals. By Denton Lotz. The Pentecostals. By Walter J. Hollenweger. The Struggle of Islam in Modern Indonesia. By B. J. Boland. The Vanishing Clergyman: A Sociological Study of the Priestly Role in South Africa. By Trevor David Verryn. The Invitation: Matthew in Mission. By Hans-Ruedi Weber. The Allied Occupation of Japan 1945–1952 and Japanese Religions. By William P. Woodard. The Life of Lt.-General Kotoka, Hero of the 24th February Revolution. By L. H. Ojosu. The Ethiopian Orthodox Church: by Aymro Wondmagegnahu and Joachim Motovu.